HIV-associated hematologic malignancies: Experience from a Tertiary Cancer Center in India - Rakesh Reddy; Ajay Gogia; Lalit Kumar; Atul Sharma; Sameer Bakhshi; Mehar C Sharma; Saumyaranjan Mallick; Ranjit Sahoo (Indian Journal of Medical and Paediatric Oncology)
Context and Aim: Data on HIV associated hematologic malignancies is sparse from India. This study attempts to analyze the spectrum and features of this disease at a tertiary cancer center in India. Setting and Methods: Retrospective study from case records of patients registered with a diagnosis of hematologic malignancy and HIV infection between January 2010 and June 2015. Results: Thirteen cases of HIV associated hematologic malignancies were identified, six of them pediatric. HIV diagnosis was concurrent to diagnosis of cancer in 12 and preceded it in one of them. ECOG PS at presentation was >1 in all of them. All patients, except one, had B symptoms. Six of the patients had bulky disease and six are stage 4. Predominant extranodal disease was seen in 67% of them. NHL accounted for 10 of 13 patients and DLBCL-Germinal center was the most common subtype. Mean CD4+ cell count was 235/μL (range, 32-494). HAART could be given along with chemotherapy to 11 patients. Two-thirds of patients received standard doses of therapy. Chemo-toxicity required hospitalization in 58%. CR was achieved in 45% and 36% had progressive disease with first-line therapy. At the time of last follow up, 3 patients were alive with responsive disease, 2 in CR and 1 in PR. None of the pediatric patients were long time responders. Conclusions: These malignancies were of advanced stage and higher grade. Goal of therapy, in the HAART era, is curative. Pediatric patients had dismal outcome despite good chemotherapy and HAART. There is an urgent need to improve data collection for HIV related cancers in India.